Keyboard warriors: kansei analysis of Malaysia's political hashtags on social media / Muhammad Danial Idris - Idris, Muhammad Danial (2014)
Kansei Engineering was initially designed to accommodate the field of product design and business process in industries. However, it is now seen as potentially suitable to be applied for the purpose of understanding the human emotions in terms of communications and psychological values. The politics in Malaysia has now evolved with the prolific rise of social media. Social media platform is now the battlefield for political parties where political terms and hashtags are bombarded each day. The aim of this research is to understand the perception of Malaysian's towards these various political hashtags and also whether a relationship exist between Kansei and the hashtags. A Kansei approach was implemented for this research which included using Kansei Words to analyse the emotional perceptions of Malaysians towards several political hashtags. From the results obtained from the research, it is evident that the general Malaysians have political awareness, sensitivity and able to respond to the hashtags that represent the various political issues in Malaysia. Additionally, Kansei was able to prove those results, hence proving the existence of relationship between Kansei and political hashtags in Malaysia. These results may be significant in providing an understanding of Malaysians response towards political issues in Malaysia, especially by the hashtags medium. Therefore, it is useful for academicians, political commentators, and political parties respectively should they wish to expand this study further or to devise better political strategies for their campaigns.